Emerging trends in flood and landslide research: single vs multi-hazard disaster analysis using GIS - Nur Shazwani Muhammad; Khairul Azmeel Mohd Sopery; Jazuri Abdullah; Mohd Syazwan Faisal Mohd; Safari Mat Desa (Penerbit Universiti Kebangsaan Malaysia, 2022)
Floods and landslides, which cause significant loss of human life and economic loss, are the most reported catastrophic events worldwide. The Geographical Information System (GIS) has been recognized as one of the most effective tools in disaster related analysis. Therefore, this article uses GIS to review the development of landslide and flood research for the past 20 years. The main elements in this review are to scrutinize the trend and scope of studies related to disaster mapping around the globe. Amongst the criteria reviewed are; details of the study area, articles that received many citations, journals with high Impact Factor scores, scope breakdown based on single and multi-hazard analysis and the theme of the study. The methodology used in this Systematic Literature Review is based on the PRISMA guidelines. Results from the review found that studies related to disaster mapping are increasing every year. This trend is influenced by data availability, efforts to produce better disaster management, frequent disaster occurrences due to climate change and evolution of GIS to analyse spatial data. Nevertheless, articles related to multi-hazard analysis are still limited, and this study suggests conducting and publishing more studies related to multi-hazard assessment in the future. This review also shows that GIS has been used widely for various types of application in disaster analysis. Articles on disaster risk assessment have been the most common. This review will help other researchers in the field of disaster management to better understand the current trend of studies related to disaster mapping.